Bromocriptine in management of large pituitary tumours. Issue 6333 (26th June 1982) - Wass, J A; Williams, J; Charlesworth, M; Kingsley, D P; Halliday, A M; Doniach, I; Rees, L H; McDonald, W I; Besser, G M
Abstract : Bromocriptine has an accepted place in the management of small pituitary tumours that secrete either prolactin or growth hormone. The treatment of large tumours with extrasellar extensions is more difficult, however: though surgery is the standard treatment, it is often unsuccessful in returning excessive hormone secretion to normal and may cause hypopituitarism. A prospective trial was undertaken to assess the frequency with which changes in pituitary function and size of large tumours occurs. Nineteen patients were studied before and during treatment with bromocriptine (7.5 to 60 ml/day) for three to 22 months, using contrast radiology and a detailed assessment of pituitary function. Eighteen patients had hyperprolactinaemia and two of these also had raised concentrations of growth hormones; one patient had an apparently non-functioning tumour. In 12 patients (63%) tumour size decreased with bromocriptine and no tumour enlarged. Nine patients had visual-field defects, which improved in seven, becoming normal in five. Pituitary function improved in nine patients (47%) becoming entirely normal in three. Bromocriptine should be the treatment of choice in patients with large pituitary tumours with extrasellar extensions, provided close supervision is maintained.